A Decade of Research on the Effectiveness of Augmented Reality on Students with Special Disability in Higher Education - Anuja Phapale; Aditya Shiledar (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This short article summarizes a decade of research on the effectiveness of augmented reality (AR) in higher education for students with disabilities in particular. The study examines how AR technology has been used to enhance the learning experience of these students. Through a comprehensive review of multiple studies and findings, this study examines the impact of AR on access, engagement, and overall educational outcomes for students with unique disabilities. The findings highlighted significant progress in the field, shedding light on the potential of AR to provide inclusive and effective learning environments for this student population, thereby contributing to a broader discussion of technical and higher education.